2012
DOI: 10.3390/molecules17044460
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of 2RS,4RS-1-[2-Phenyl-4-[2-(2-trifluromethoxy-phenoxy)-ethyl]-1,3-dioxolan-2-yl-methyl]-1H-1,2,4-triazole Derivatives as Potent Inhibitors of Brassinosteroid Biosynthesis

Abstract: Brassinosteroids are important phytohormones that affect many aspects of plant growth and development. In order to manipulate brassinosteroid levels in plant tissues by using specific biosynthesis inhibitors, we have carried out a systemic search for specific inhibitors of brassinosteroid biosynthesis. Synthesis of triazole derivatives based on the ketoconazole scaffold revealed a series of novel brassinosteroid biosynthesis inhibitors (the YCZ series). To explore the structure-activity relationships of this s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 24 publications
1
22
1
Order By: Relevance
“…1) as currently the most potent inhibitor of BR biosynthesis found to date. [30][31][32] The use of YCZ-18, an analog of yucaizol (the structure is shown in Fig. 1), demonstrated that yucaizol is a specific inhibitor of BR biosynthesis that binds to purified recombinant CYP90D1.…”
mentioning
confidence: 99%
“…1) as currently the most potent inhibitor of BR biosynthesis found to date. [30][31][32] The use of YCZ-18, an analog of yucaizol (the structure is shown in Fig. 1), demonstrated that yucaizol is a specific inhibitor of BR biosynthesis that binds to purified recombinant CYP90D1.…”
mentioning
confidence: 99%
“…The brassinosteroid biosynthesis inhibitor compound library was synthesized by a method that was described previously Yamada et al 2012Yamada et al , 2013. Stock solutions of the test compound were dissolved in dimethyl sulfoxide (DMSO) at a concentration of 100 μM, and stocked at −30°C.…”
Section: Chemicalsmentioning
confidence: 99%
“…The methods for preparing the target compound Ga-Gj are similar to those for preparing compound 7a as outlined in scheme 2, except for the final step: variant structures at ring B were introduced by using different phenols. Data for the characterization of the test compounds using Nuclear Magnetic Resonance (NMR) and High Resolution Mass Spectrometry (HR-MS), were achieved and were shown in our previous reports Yamada et al 2012).…”
Section: Chemistrymentioning
confidence: 99%
“…Based on the molecular scaffold of ketoconazole, a widely used P450 inhibitor, we discovered a series of new BR biosynthesis inhibitors [10]. Structure-activity relationship studies of triazole type BR biosynthesis inhibitor revealed a series of potent inhibitor of BR biosynthesis [11]- [13]. To determine the binding affinity of this synthetic series to CYP90D1, a BR biosynthesis enzyme, by using an analogue of YCZ-18 gave evidence that YCZ-18 binds to CYP90D1 with a Kd value of 0.79 M [14].…”
Section: Introductionmentioning
confidence: 99%